OBSERVATION OF INTERFERENCE OF NEUTRONS REFLECTED FROM THIN-FILMS - Hayter, J; Penfold, J; Williams, W (1976)
DURING measurements of the reflection of neutrons from metallic thin films, we have observed an optical interference phenomenon analogous to the interference of light reflected from plane parallel plates; the experimental arrangement is the neutron analogue of the Lummer-Gehrcke interferometer 1. © 1976 Nature Publishing Group.